Upaya Meningkatkan Kemampuan Guru dalam Pengelolaan PBM Melalui Kegiatan Supervisi Akademik dengan Pendekatan Kolaboratif di SD Negeri Cerih 03 Kecamatan Jatinegara Kabupaten Tegal Semester 1 Tahun Pelajaran 2019/2020 - Slamet Panca Marindo (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This research aims to determine the implementation and improvement of teachers' abilities in managing PBM through the implementation of academic supervision with a collaborative approach at SDN Cerih 03 Semester 1 of the 2019/2020 Academic Year, especially in the aspect of managing teaching and learning activities. This type of research is school action research. The method and design of this school action research was carried out with research procedures based on the principles of Kemmis and Taggart (1988:10) which included the following activities: (1) planning (planning), (2) implementing action (action), 3) observation (observation). ) , (4) reflection (reflection). The research subjects were teachers at SDN Cerih 03 in Semester 1 of the 2019/2020 academic year as many as 7 teachers. Data collection techniques using observation, and documentation studies. The validity of the data using triangulation, namely the triangulation used in the research is triangulation of data sources and triangulation of methods. Data analysis used qualitative analysis. The results showed an increase in the ability of teachers in the management of the teaching and learning process (PBM), where in the initial conditions there were no teachers who were able to develop the management of the teaching and learning process (PBM) properly, this was evidenced by the low average score obtained by the teachers. namely 49.00 and only included in the Less category, In the first cycle it increased significantly and there were 2 teachers or 28.57% who were stated to be able to manage the teaching and learning process (PBM) well, with a classical average score of 66, 57 and included in the ENOUGH criteria and in the second (last) cycle he became a teacher or 100%, as evidenced by the classical score of 84.29 in the GOOD score criteria. From the results of the research as described above, it can be concluded that the implementation of academic supervision with a collaborative approach at SDN Cerih 03 Semester 1 of the 2019/2020 academic year has proven to be able to improve the ability of teachers in managing PBM.